2021
DOI: 10.1002/cbic.202100139
|View full text |Cite
|
Sign up to set email alerts
|

Binding Mode Characterization of Osteopontin on Hydroxyapatite by Solution NMR Spectroscopy

Abstract: Extracellular matrix glycoproteins play a major role in bone mineralization and modulation of osteogenesis. Among these, the intrinsically disordered protein osteopontin (OPN) is associated with the inhibition of formation, growth and proliferation of the bone mineral hydroxyapatite (HAP). Furthermore, post‐translational modifications like phosphorylation can alter conformations and interaction properties of intrinsically disordered proteins (IDPs). Therefore, the actual interaction of OPN with a HAP surface o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 67 publications
(154 reference statements)
0
3
0
Order By: Relevance
“…Although OPN exists in solution as an intrinsically disordered protein, it is hypothesized that binding to one or more of its partners induces a defined tertiary structure in the locality of the interaction that serves as the binding surface. This hypothesis has been confirmed by experiments in which structures of OPN bound to hydroxyapatite have been determined by NMR [ 47 , 48 ]. Thus, OPN may regulate the crystallization of calcium phosphate when hydroxyapatite is being laid down in bone formation.…”
Section: Opn Protein Structurementioning
confidence: 75%
“…Although OPN exists in solution as an intrinsically disordered protein, it is hypothesized that binding to one or more of its partners induces a defined tertiary structure in the locality of the interaction that serves as the binding surface. This hypothesis has been confirmed by experiments in which structures of OPN bound to hydroxyapatite have been determined by NMR [ 47 , 48 ]. Thus, OPN may regulate the crystallization of calcium phosphate when hydroxyapatite is being laid down in bone formation.…”
Section: Opn Protein Structurementioning
confidence: 75%
“…Several studies have demonstrated such behaviors, with typical observations that phosphorylation expands neutral or negatively charged IDPs, and shrinks positively charged IDPs [28,61,68]. For example, a recent study used NMR to demonstrate that hyperphosphorylated osteopontin becomes extended, thereby preventing correct biomineralization of the bone mineral hydroxyapatite and causing dystrophic calcification [69]. However, a general principle remains difficult to extract due to the number of other parameters at play.…”
Section: Impacting the Chemistry And The Conformational Ensembles Of ...mentioning
confidence: 99%
“…The analysis of OPN's amino acid residues reveals its robust binding ability to calcium ions, particularly on the crystal's (100) surface 15 17 . Studies modifying OPN's conformation through phosphorylation enhance its binding affinity to the HAP surface 18 21 . Amino acid residues containing carboxyl groups, like aspartic acid and glutamic acid, play a pivotal role in the interaction between proteins and crystals, as confirmed by molecular dynamics simulations of OPN adsorption 22 , 23 .…”
Section: Introductionmentioning
confidence: 99%